Legal Document Control: A Basic Condition to Protect and Ensure Human Rights - Que, Hoang Thi Kim; Nga, Le Thi Phuong (VNU Journal of Science: Legal Studies, 2019)
This article analyzes the significance of legal document control, one of the basic conditions to protect human rights and ensure freedom and constitutional, legitimate interests. Although the Vietnamese legal system is more and more complete, there are limitations to its legal document control. The article shows the clear negative influences of inappropriate legal regulations on human rights and interests. On that basis, the article referred to the basic rules of legal document control: The control of constitutionality, lawfulness and rationality throughout the legal document formulation process. Keywords: Legal supervision, supervision of legal documents, mechanisms for supervising legal (normative) documents, constitutionality, legitimacy, profitability. References: [1] Đức Minh, “Thủ tướng: pháp luật phải kiểm soát quyền lực nhà nước”. https://plo.vn/thoi-su/thu-tuong-phap-luat-phai-kiem-soat-quyen-luc-673489.html. [2] Bộ Tư pháp, Ban hành văn bản trái pháp luật thể hiện sự "nhờn" luật. https://nld.com.vn/thoi-su/bo-tu-phap-ban-hanh-van-ban-trai-phap-luat-the-hien-su-nhon-luat-20180808091902444.htm. [3] Nguyễn Bá Chiến, Pháp luật triệt tiêu pháp luật, Tạp chí Nghiên cứu lập pháp, số 74, tháng 4/2006. [4] Thế Kha, Phó Thủ tướng chỉ đạo xử lí các văn bản trái luật. https://dantri.com.vn/xa-hoi/pho-thu-tuong-chi-dao-xu-ly-cac-van-ban-trai-luat-20180815220104277.htm. [5] Đinh Dũng Sỹ, Chính sách và mối quan hệ giữa chính sách với pháp luật trong hoạt động lập pháp, Tạp chí Nghiên cứu Lập pháp, số 127, tháng7/2008. [6] Phạm Chi Lan, Thể chế cho một chính phủ kiến tạo. http://www.doanhnhansaigon.vn/van-de/the-che-cho-mot-chinh-phu-kien-tao/1102398. [7] Thái Bình, Không cài cắm vào luật để phục vụ lợi ích riêng. http://vietnamnet.vn/vn/thoi-su/chinh-tri/thu-tuong-khong-cai-cam-vao-luat-noi-dung-khong-vi-loi-ich-chung-348136.html#inner-article [8] Ann Seidman, Robert B. Seidman, Nalin Abeyesekers, Soạn thảo luật pháp vì tiến bộ xã hội dân chủ: Sổ tay cho nhà soạn thảo, NXB. Chính trị Quốc gia, (2003) 70 - 72. [9] Nguyễn Thị Cẩm Tú, Công tác kiểm tra văn bản quy phạm pháp luật thuộc trách nhiệm của Bộ Tư pháp. http://tcdcpl.moj.gov.vn/qt/tintuc/Pages/thi-hanh-phap-luat.aspx?ItemID=377. [10] Nguyễn Minh Đức, Triệt tiêu tình trạng cài cắm chính sách trong xây dựng pháp luật. https://thanhnien.vn/chinh-tri/triet-tieu-tinh-trang-cai-cam-chinh-sach-trong-xay-dung-phap-luat-978708.html. [11] https://thuvienbinhphuoc.org.vn/chinh-tri/thu-tuong-khong-de-ai-bi-bo-sot-trong-chinh-sach-phat-trien-3746.html.